Nutritional interventions in cancer patients - Krawczyk, Joanna; Świeboda-Sadlej, Anna (Contemporary Oncology/Współczesna Onkologia, 2010)
The nutritional status in the majority of patients with malignancies is already impaired at the moment of cancer diagnosis, whereas progressive loss of body mass is one of the most frequent symptoms of cancer. Malnutrition is a significant cause of impaired response to therapy and increased susceptibility to treatment-related adverse effects and complications, as well as worsening quality of life. The aetiopathogenesis of these problems is complex. Thus, under-nutrition/cancer cachexia may be a result of both the presence of tumour and the adverse effects of therapeutic procedures. Nutritional management should begin with the assessment of nutritional status. It should be performed adequately often and suitable nutritional interventions ought to be applied when considered necessary. Nutritional treatment should consist of planned supply of exactly selected nutritional elements. The enteral and/or parenteral routes need to be used. The nutritional management may also require pharmacological support, because a simple increase of supply of nutritional elements may be insufficient for adequate reduction of hypercatabolic processes and to achieve an increase of body mass. Nutritional interventions are an inherent element of optimal complex care for people with cancer.